2019
DOI: 10.1002/cptc.201900256
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Optical Properties of Triarylboranes with Strongly Electron‐Accepting Bis(fluoromesityl)boryl Groups: when Theory Meets Experiment

Abstract: The photophysical properties (absorption, fluorescence and phosphorescence) of a series of triarylboranes of the form 4‐D−C6H4−B(Ar)2 (D=tBu or NPh2; Ar=mesityl (Mes) or 2,4,6‐tris(trifluoromethylphenyl (Fmes)) were analyzed theoretically using state‐of‐the‐art DFT and TD‐DFT methods. Simulated emission spectra and computed decay rate constants are in very good agreement with the experimental data. Unrestricted electronic computations including vibronic contributions explain the unusual optical behavior of 4‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
1
6
0
Order By: Relevance
“…As such, the transition can be classified as a charge transfer (CT) transition. Similar observations were made for our previously reported D ‐π‐A systems with B( F Xyl) 2 , B( F Mes) 2 or BMes 2 as the acceptor . In accordance with a CT transition, the emission maximum of 1 shifts bathochromically with increasing solvent polarity ( λ max, em =484, 532, and 590 nm in hexane, toluene and THF, respectively).…”
Section: Resultssupporting
confidence: 89%
“…As such, the transition can be classified as a charge transfer (CT) transition. Similar observations were made for our previously reported D ‐π‐A systems with B( F Xyl) 2 , B( F Mes) 2 or BMes 2 as the acceptor . In accordance with a CT transition, the emission maximum of 1 shifts bathochromically with increasing solvent polarity ( λ max, em =484, 532, and 590 nm in hexane, toluene and THF, respectively).…”
Section: Resultssupporting
confidence: 89%
“…54 While most studies have focused on Mes 2 B groups as acceptors, Marder and co-workers found that the much enhanced acceptor strength of (FMes) 2 B (FMes = 2,4,6-tris(trifluoromethyl)phenyl) derivatives can be beneficial for optoelectronic application. 55,59 These findings prompted us to investigate the photophysical properties of our polymers and model compounds in more detail.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Triphenylamines possessed a characteristic propeller-like structure and were frequently employed in the construction of AIE fluorophores. 28 Lu and co-workers designed a series of phenylmethylene pyridineacetonitrile derivatives bearing a triphenylamine (TPA) structure and pyridine ring with the nitrogen atom at the ortho (36), meta (37), and para (38) position in Figure 5c. 29 In tetrahydrofuran (THF), their fluorescence lifetimes were only approximately 1 ns, but in the solid state, these lifetimes were significantly extended.…”
Section: Intramolecular and Intermolecular Interactionsmentioning
confidence: 99%
“…This conjugated structure facilitated efficient electron transfer within the molecule, leading to reduced nonradiative energy loss and, consequently, longer fluorescence lifetimes. Halet and co-workers performed DFT and time-dependent (TD) DFT calculations to investigate the photophysical properties of a series of triarylborane derivatives 52 – 54 (Figure a, 52–54) …”
Section: Strategies For Fluorescence Lifetime Control Of Small Moleculesmentioning
confidence: 99%